Peran Inspektorat Daerah Dalam Rangka Pengawasan Penyelenggaraan Pemerintahan di Semarang - Amelia Siti Nurul Hamidah; Andi Tenridala Ariani; Fathia Rahma Sholikhah; Zalzabila Puteri Herdini; Ivan Darmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Implementation of Village Law no. 6 of 2014 had a positive impact by disbursing quite large funds to villages throughout Indonesia. As a village head, a village head must be able to carry out management functions, namely planning, organizing, implementing and supervising so that his village progresses. This research uses a literature study method looking at various journals and other reading sources. Based on the research results found, the Semarang City National Land Office knows and understands the positive fictitious rules, but they cannot be fully implemented because the office has standard operational rules (SOP) which must also be obeyed. followed. obeyed. The application of positive fictitious provisions in practice is still not very effective in improving the quality of public services. The effect of positive fictitious orders seems to be to make state managers leave because they conflict with institutional SOPs. There are several obstacles in implementing this provision, including that state institutions and/or government officials and the public do not understand this provision properly and correctly, and court decisions that grant the petition cannot be trusted in practice. This decision offer again contradicts the SOP of each institution. The solution to the various obstacles is the need to deepen understanding of positive fictitious regulations for both the authorities and the public, and the need to design government regulations that provide more detailed and more enforceable implementation guidelines.